2019
DOI: 10.1002/ajhb.23305
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and functional fitness of 9‐ to 10‐year‐old Chilean children

Abstract: Objective: This study aimed to determine the association between body mass index (BMI) and functional fitness (FF) in 9-to 10-year-old Chilean children. Methods: This was an analytical and cross-sectional study with a probabilistic sample consisting of 139 children of both sexes. Anthropometric measurements, hemodynamic variables, physical activity (PAQ-C), and FF (measured by a 6-minute walk test: 6MWT) were recorded. If the distance walked was <10th percentile, FF was considered low. Means of variables betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…An interesting research finding is the decrease in subjects with obesity category from 29.6% to 25.9% after the application of baseball games. The results confirm previous research findings about the effect of increased physical activity on decreasing body mass index in children (Gatica-Domínguez et al, 2018;Maury-Sintjago et al, 2019;Mora-Gonzalez et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…An interesting research finding is the decrease in subjects with obesity category from 29.6% to 25.9% after the application of baseball games. The results confirm previous research findings about the effect of increased physical activity on decreasing body mass index in children (Gatica-Domínguez et al, 2018;Maury-Sintjago et al, 2019;Mora-Gonzalez et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, the performance differences between NO and OW subjects were not so appreciable at sea level, similar to the findings of Pathare, Haskvitz and Selleck who reported no statistical difference between NO and OW children ( p = 0.899) at sea level [ 47 ]. Moreover, previous studies carried out at sea level using the 6 MWT have shown that overweight and obese children and adolescents had lower physical fitness than NO children [ 48 , 49 , 50 ]. The differences on submaximal exercise performance at HA in obese children could be explained by the deficient O 2 uptake at HA and higher demand ventilation, increased work related to breathing, respiratory muscle inefficiency and diminished respiratory compliance given their anthropometric characteristics [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relation of overweight and obesity or rather higher BMI-categories with inferior performances in motor tests was recognized during the last years [62][63][64][65][66][67][68][69] (see Table 2). For example, Zaqout et al [65] who examined the effect of PF on cardiometabolic risk factors found a strong correlation between higher waist circumference and both lower limb strength and cardiorespiratory fitness in European children (6-11 years).…”
Section: Body Composition As a Health Indicator In Motor Testingmentioning
confidence: 99%